HEBAT: A Reality-Based Group Guidance Program to Build Students’ Disciplined Character - Shelly Tanaya Dhayinta; Muliono; Eka Sudibya; Bambang Widjanarko (Universitas Kristen Cipta Wacana, 2026)
Low disciplinary character is still one of the problems frequently encountered in Junior High School (SMP) students, which is indicated by the behavior of arriving late, not complying with school rules, not completing assignments on time, and low responsibility in participating in the learning process. This condition shows that the formation of disciplinary character requires an approach that is not only oriented towards giving sanctions, but also able to foster students' awareness and responsibility for each chosen behavior. This community service activity aims to shape the disciplined character of students through the HEBAT Program (Effective Life with Character, Responsibility, and Obedience) which uses Realita Counseling-based group guidance services. The program was implemented for 10 students of SMP Negeri 1 Kauman, Tulungagung Regency, who were selected based on the results of a needs assessment by the Guidance and Counseling teacher. The implementation method uses the Participatory Action Service (PAS) approach which includes the preparation stage, the implementation of five group guidance sessions with the Wants, Doing, Evaluation, Planning (WDEP) approach, evaluation through pretests and posttests, behavioral observations, and follow-up with the BK teacher. The results of the activity showed an increase in students' understanding of the character of discipline, marked by an increase in the category of good understanding from 20% to 80%. Observations also showed an increase in disciplined behavior, such as punctuality in school attendance, compliance with rules, responsibility in completing assignments, and the ability to control behavior during learning. All participants responded positively to the program implementation and stated that they were motivated to maintain disciplined behavior in their daily lives. Thus, the HEBAT Program has proven to be an alternative group guidance service that is effective, applicable, and has the potential to be replicated as a model for strengthening disciplinary character education in schools.